"Where are we going to go now?" European Union migrants' experiences of hostility, anxiety, and (non‐)belonging during Brexit. Issue 1 (27th September 2018) - Guma, Taulant; Dafydd Jones, Rhys
Abstract: This paper examines the impact of the 2016 European Union (EU) referendum and its aftermath from the perspective of European migrants living in Wales. Drawing on interviews conducted with EU nationals in 2016 and 2017, the article highlights various examples of hostility and violence encountered by these migrants during and after the referendum campaign, demonstrating the longstanding nature of hostile experiences. It further outlines the uncertainty and insecurity experienced during this period, noting how Brexit affected not only EU migrants' rights and entitlements but also their settlement and sense of identity and belonging. The analysis sheds light on various negative emotions and reactions triggered by the referendum, illustrating the diversity of migrants' experiences. Highlighting the multiple and complex ways in which the referendum affected the migrants, the article argues that Brexit should be understood as an ongoing process of "othering" and unsettling.